2013
DOI: 10.3945/jn.113.181461
|View full text |Cite
|
Sign up to set email alerts
|

Differential Bioavailability, Clearance, and Tissue Distribution of the Acyclic Tomato Carotenoids Lycopene and Phytoene in Mongolian Gerbils

Abstract: Lycopene (LYC) is the major tomato carotenoid and is the focus of substantial research. Phytoene (PE), a minor tomato carotenoid, is found in human blood and tissues in similar concentrations to LYC. To determine which metabolic differences underlie this phenomenon, Mongolian gerbils (Meriones unguiculatus, n = 56) were fed control or tomato powder (TP)-containing diets (to establish steady-state serum and tissue carotenoid concentrations similar to tomato-fed humans) for 26 d. The TP-fed gerbils were then pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Interestingly, it was observed that almost all extra-hepatic tissue accumulated more radioactivity after labeled-phytoene than labeled-lycopene dosing. Altogether, the data from this interesting study confirmed that there are important differences between these two carotenoids in bioavailability, tissue accumulation and clearance [124].…”
Section: Mongolian Gerbilssupporting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, it was observed that almost all extra-hepatic tissue accumulated more radioactivity after labeled-phytoene than labeled-lycopene dosing. Altogether, the data from this interesting study confirmed that there are important differences between these two carotenoids in bioavailability, tissue accumulation and clearance [124].…”
Section: Mongolian Gerbilssupporting
confidence: 71%
“…On the other hand, the tomato supplementation significantly decreased the multiplicity of inflammatory and altered hepatic foci in the liver of HFD-fed rats [123]. Contrastingly, no changes in inflammatory markers were observed in a study referred to before where gerbils were fed tomato powder plus lycopene or phytoene [124].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…This provides rationale to feeding tangerine tomatoes when increasing tissue lycopene is desirable, and contrary to others who have found that phytoene is more bioavailable than lycopene 25, 26 .…”
Section: Resultsmentioning
confidence: 88%
“…Serum and diet samples were analyzed by HPLC using a photodiode array detector (HPLC-PDA) (PDA 2996, Waters, Milford, MA). The HPLC system and carotenoid standard preparation have been previously described (49). The analytical lab participates semi-annually in the National Institute for Standards and Technology’s Fat Soluble Vitamin and Carotenoid Round Robin activity to monitor protocol accuracy with respect to other analytical labs.…”
Section: Methodsmentioning
confidence: 99%